POTENSI BAKTERI Serratia sp. SEBAGAI AGENSIA HAYATI PENYAKIT JAMUR AKAR PUTIH (Rigidoporus microporus) - Cici Indriani Daliminthe; Ahmad Dahlan; Radite Tistama (Jurnal Agro Estate, 2019)
Serratia sp is the family Enterobacteriaceae gram-negative bacteria that have flagella Peritrik, motile and reported to be anti-fungal. Chitinolytic chitinase activity of bacteria are potentially used as a biological control against pathogenic fungi.The purpose of this research is to know the potential of bacteriaSerratia sp in controlling white root rot disease caused by Rigidoporus microporus on the rubber plant in polibag. This research uses a randomizedblock design (RAK) nonfaktorial with 5 treatments and 5 replications. Parametersmeasured were extensive white root fungus colony growth (cm) in the laboratory,white root fungus attack intensity (%) in polybag, the percentage of inhibition (%)in polybag and visual symptom of the white root fungus attack in polybag. Thereault of this showed that Serratia sp bacteri application infection very obvious inobstructing extensive growth of the white root fungus colony in Laboratory, withthe lowest extensive of colony 3,06 cm on D4 standard (10ml/100 ml PDA) A verysignificant effect in reducing the intensity of white root fungus attacks the inhibition rate reached 54%, or healing reached 47,31% the age of 6 weeks after application.